Daily iron supplementation for improving anaemia, iron status and health in menstruating women - Low, MSY; Speedy, J; Styles, CE; De-Regil, LM; Pasricha, S-R (Cochrane Collaboration, 2016)
Background Iron‐deficiency anaemia is highly prevalent among non‐pregnant women of reproductive age (menstruating women) worldwide, although the prevalence is highest in lower‐income settings. Iron‐deficiency anaemia has been associated with a range of adverse health outcomes, which restitution of iron stores using iron supplementation has been considered likely to resolve. Although there have been many trials reporting effects of iron in non‐pregnant women, these trials have never been synthesised in a systematic review.